Réponses

2013-05-05T19:45:22+02:00

E= 10x + 15 + 12x + 6 = 22x + 21

F= 12x - 24 - 12 + 15x = 27x - 37

G= 3x + 5 + 4x - 8 = 7x - 3

H = 2x -7 -4x -3 = -2x - 10

 

J'espère que c'est juste et de t'avoir aidé

2013-05-05T19:56:15+02:00

e) 5*2+5*3+3*4x+3*2= 10+15+12x+6=31+12x

 

f) 6*2x+6*(-4)-3*4-3*(-5x)=12x-24-12+15x=-36+27

 

g) 3x*4x+3x*(-8)+5*4x+5*(-8)= 12x²-24x+20-40=12x²-24x-20

 

h) 2x*4x+2x*3-7*4x-7*3=8x²+6x-28x-21=8x²-22-21

 

                     voila et jepere que je t'ai aidé :-)